Toward Advanced Nursing Practice along with People-Centered Care Partnership Model for Sustainable Universal Health Coverage and Universal Access to Health - Tomoko Kamei; Keiko Takahashi; Junko Omori; Naoko Arimori; Michiko Hishinuma; Kiyomi Asahara; Yoko Shimpuku; Kumiko Ohashi; Junko Tashiro
ABSTRACT Objective: this study developed a people-centered care (PCC) partnership model for the aging society to address the challenges of social changes affecting people's health and the new role of advanced practice nurses to sustain universal health coverage. Method: a people-centered care partnership model was developed on the basis of qualitative meta-synthesis of the literature and assessment of 14 related projects. The ongoing projects resulted in individual and social transformation by improving community health literacy and behaviors using people-centered care and enhancing partnership between healthcare providers and community members through advanced practice nurses. Results: people-centered care starts when community members and healthcare providers foreground health and social issues among community members and families. This model tackles these issues, creating new values concerning health and forming a social system that improves quality of life and social support to sustain universal health care through the process of building partnership with communities. Conclusion: a PCC partnership model addresses the challenges of social changes affecting general health and the new role of advanced practice nurses in sustaining UHC.